Undermining People's Freedoms and Opinions in the Digital Era - Muhammad, Hasanuddin; Liyorba Indra, Gandhi; Rizka Virnanda, Olivia (KnE Social Sciences, 2024)
The transition of media that conveys freedom of expression and opinion from mass media to online media has given rise to the phenomenon of cybercrime. As a result, there is weakening of freedom of expression and opinion. In fact, according to the data in 2020-2021, there were 44 cases related to freedom of expression and opinion. This paper aims to look at the impact and the reasons behind the occurrence of cyberattacks. This research is included in socio-legal research with secondary data sources. The data search process uses documentation and analysis using an interdisciplinary approach. The result is that cybercrime is carried out in the form of hacking, doxing, and cyberbullying. The impact was a violation of the principles of human rights and democracy, causing fear in the community. Crimes in the form of hacking, doxing, and cyberbullying occur because they are effective in protecting political interests and putting pressure on society, also it is difficult for perpetrators to be prosecuted legally. Keywords: hacking, doxing, cyberbullying